2015
DOI: 10.1308/003588415x14181254789727
|View full text |Cite
|
Sign up to set email alerts
|

Palatal and retropharyngeal injury secondary to intubation using the GlideScope® video laryngoscope

Abstract: Introduction There are few reports of injury to the soft palate and retropharynx sustained during intubation with the GlideScope® video laryngoscope. Most reports are of isolated injury to the soft palate. Case History We describe a patient in whom the retropharynx was injured but the extent of the injury was not observed initially. The patient did not suffer severe sequelae from this injury. However, this injury can cause serious sequelae if it is not recognised (eg development of a retropharyngeal abscess). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Many authors suggest that injury most likely occurs during blind introduction of the endotracheal tube into the oropharynx, while the operator is focused on the video monitor instead of the oral cavity [12]. Thusly, emphasis has been placed on ensuring the endotracheal tube is directly seen passing into the oral cavity before attention is diverted to the video monitor [8]. Risk for injury can be further increased with the use of rigid stylets, and as such, softer malleable stylets are recommended [8,12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many authors suggest that injury most likely occurs during blind introduction of the endotracheal tube into the oropharynx, while the operator is focused on the video monitor instead of the oral cavity [12]. Thusly, emphasis has been placed on ensuring the endotracheal tube is directly seen passing into the oral cavity before attention is diverted to the video monitor [8]. Risk for injury can be further increased with the use of rigid stylets, and as such, softer malleable stylets are recommended [8,12].…”
Section: Resultsmentioning
confidence: 99%
“…Thusly, emphasis has been placed on ensuring the endotracheal tube is directly seen passing into the oral cavity before attention is diverted to the video monitor [8]. Risk for injury can be further increased with the use of rigid stylets, and as such, softer malleable stylets are recommended [8,12].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tracheal intubation can cause various acute airway injuries, including: arytenoid subluxation; supraglottic or glottic haematoma; laceration of the glottic mucosa and vocal cord; tracheal rupture; and mediastinal emphysema . Some supraglottic injuries, such as perforation of the soft palate, palatoglossal arch and palatopharyngeal arch, have been reported with the Glidescope ; possible reasons include the use of excessively large blades, rigid stylets, and unnecessary force during intubation . Jeon et al suggested that a forceps‐guided tube exchanger is better than a stylet in decreasing the incidence of sore throat when intubating with the Glidescope .…”
Section: Introductionmentioning
confidence: 99%